Insulin in human milk: postpartum changes and effect of gestational age. Issue 3 (1st March 2003) - Shehadeh, N; Khaesh-Goldberg, E; Shamir, R; Perlman, R; Sujov, P; Tamir, A; Makhoul, I R
Abstract : Objective: To determine if human milk insulin (HMI) concentrations are affected by gestational age and postnatal age. Design and setting: An observational study carried out in a level III neonatal intensive care unit. Insulin concentrations were determined in human milk of 90 parturient mothers who delivered between 30 and 41 weeks gestation. Samples were collected on days 3 and 10 after delivery. Results: HMI concentrations for mothers of preterm infants were not significantly different from those of full term infants, on either day 3 or 10 post partum. When results for all 90 mothers were pooled, regardless of gestational age, HMI concentration fell significantly from day 3 to day 10 (50.1 (34.6) v 41.1 (28.5) μU/ml; p = 0.01; mean (SD)). However, this decrease was only significant for mothers delivering at term (37–41 weeks). Conclusions: HMI concentrations were not influenced by gestational age at delivery. They decreased post partum, mainly in mothers of term infants. The postnatal changes in HMI concentrations and the effects of oral insulin on the immature intestinal mucosa warrant further investigation.